Pregnancy with Pre-existing Heart Disease- Analysis of 50 Cases - Kulsum, Umme; Qumruzzaman, Khondoker; Wahid, Fatima; Begum, Zakia; Mannan, Khadija; Islam, Nilufar Islam; Parveen, Tabassum; Akhtar, Nahreen (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Objective: The aim of this study was to evaluate the maternal and fetal outcome with maternal pre- existing heart disease during pregnancy in terms of maternal complication, fetal complication & mode of delivery. Materials & Methods: This retrospective cohort study was carried out over a period of 2 years (Jan’2022-Dec 2023) in Fetomaternal Medicine Department, BSMMU involving 50 admitted pregnant patients with pre-existing heart disease. All cases were followed during pregnancy, labor & early puerperium. Results: Age of the patient ranging from 18-30 years, most (38.33%) belonged to the age group 20-25 years and five (09.26%) belonged to > 30 years of age group. Most of the patients 17 (34%) were 2nd gravida (34%). Among 50 patients 38 (76%) received regular antenatal checkup. Thirty five (70%) of patients suffered from rheumatic heart disease. Among rheumatic heart disease isolated mitral stenosis (32%) was the predominant cardiac lesion, while atrial septal defect (14%) was the most common form of congenital heart disease. Based on New York Heart Association (NYHM) functional classification. 76% women were in class-I. The rate of Cesarean Section (85.71%) was high in study subjects. The rate of prematurity was high in class II. No baby was delivered stillborn and there was no neonatal death. Out of fifty patients, eight patients developed heart failure during their hospital stay. The duration of stay was shortened in class I. Two patients of study subject died one from class II and one from class III. Conclusion: Pregnancy with preexisting heart diseases associated with good maternal & fetal outcome in NYHA class I group. Bangladesh J Obstet Gynaecol, 2024; Vol. 39(2): 98-103